Perspective Chapter: iPEAR-MOOC - Wunder, Iris; Maloszek, Ruth (Massive Open Online Courses - Current Practice and Future Trends [Working Title], 2023)
Augmented Reality (AR) has been developing rapidly in the past years, and the acceptance of this technology is growing amongst the users of smartphones and tablets. Educational applications and resources that use AR technology are also growing in both number and quality. However, most educators lack sufficient digital skills and are unaware of the pedagogical approaches necessary to use the available digital tools to advance their teaching practices and their professional development. An international team of researchers from the Friedrich-Alexander-Universität Erlangen-Nürnberg (Germany), NTNU (Norway), AETMALab (Greece), Akto (Greece) and Eucen (Spain) started an EU-funded project to explore the possibilities of engaging higher education students by combining AR And peer learning. As part of the project, a MOOC started in October 2022 (https://imoox.at/course/ipear) to share the iPEAR approach created by the project group. In this 4-week course, students learn about AR tools, pear learning, and how to implement the combination of both into their seminars. Participants work in peer groups to create a first augmentation and provide a pedagogical background for their projects. The chapter will describe the experiences with and results from the MOOC.<br
Keywords: MOOC; iPEAR